Microwave-Assisted, Preparation, Characterization, and Biological Activities of Schiff Bases Derived from 4-Aminoantipyrine with Acetonyl Acetone for Some New Rare-Earth Metals - Hussein, Kawther Adeeb; Shaalan, Naser; Faeq, Marwa (Universitas Gadjah Mada, 2024)
Five new lanthanide complexes based on azomethine (Schiff bases) ligands have been synthesized, including La, Nd, Er, Gd, and Dy. Complexes were synthesized using the azomethine Schiff bases resulting from condensation reactions between 4-aminoantipyrine and acetonylacetone. The structural characteristics of azomethine obtained are characterized quantitatively and qualitatively through various techniques, including elemental analyses, magnetic susceptibility measurement, molar conductivity, infrared, ultraviolet absorption, GC-mass, and 1H- and 13C-NMR spectroscopy studies. The structural characteristics of Ln+3 complexes indicate that the complexes possess a composition of a specific type. Based on the elemental analyses, magnetic susceptibility measurement, molar conductivity, and ultraviolet absorption spectroscopy data, it can be inferred that the central metal ion is surrounded by a coordination number of 10, the general formula of [Ln(L)2(NO3)]·nNO3nH2O. The physical measurements confirmed that the synthesized complexes exhibit non-electrolyte behavior and paramagnetic properties. The antibacterial activity of the compounds was assessed in vitro against 4 pathogenic strains: E. coli, S. aureus, K. pneumoniae, and S. mutans. The evaluation was conducted using the agar disc spreading method. The results demonstrated that certain complexes exhibited significant antibacterial efficacy in comparison to the biological activity of the ligand.